THE IMPACT OF RACISM ON THE MENTAL HEALTH OF BLACK WOMEN: AN ANALYSIS AT THE UNIVERSITY SCHOOL - Inácio Gomes, Larissa; Campos de Souza Amaral, Shirlena; do Rosario Silva, Gabriela (LINKSCIENCEPLACE, 2026)
The article in question aims to address the relationship between race and mental health in general, starting from the point of view that this has been forgotten in Brazilian thought, especially due to the consequences of a possible racial democracy in Brazil. However, it is necessary to think beyond this, which implies observing the strong evidence that such a democracy would be far from promoting equality regardless of race or ethnicity, since, for example, racism emerged from contexts that emphasize racial theories, but at the beginning of the 20th century it entered practices in various contexts, and one of them is the university. The methodology applied in this research is qualitative and bibliographic (Marconi; Lakatos, 2017). Studies are developed focused on the dimensions between racism and the mental health of black women, highlighting the possible impact on the university.